Rescate de la gastronomía tradicional de la zona rural del cantón Montúfar - Pantoja Rosero, Darwin Javier (2024)
The project focused on rescuing and standardizing five traditional preparations from the rural area of Montúfar canton, Carchi province, where there has been a significant loss of ancestral culinary methods and the oblivion of typical dishes. This phenomenon affects the local gastronomic identity and limits the tourism potential of the region. The general objective was to standardize these preparations through their preparation and tasting, in order to preserve the gastronomy of Montufre and promote its revitalization. To achieve this objective, three specific objectives were proposed: to identify a little-known traditional dish in each of the five parish capitals of the canton, to standardize the recipes through their preparation and tasting, and to design a recipe book that documents the recipes and their histories. The methodology included qualitative research through interviews with people knowledgeable about the culinary traditions, an experimental approach for the standardization of the recipes, and a descriptive analysis for the elaboration of the recipe book. The results showed the recovery of five traditional recipes: locro de la Marita, locro de cuy, locro de hoja tender de zambo, poleada and nettle leaf soup. The creation of the recipe book not only made it possible to preserve these preparations, but also to highlight the history and culture of each area. In conclusion, the research underscores the importance of rescuing the culinary traditions of the Montúfar canton, with the potential to revitalize its gastronomic identity and promote tourism.